Times of sowing and spacing on the production of lupine phytomass - Benassi, Antonio Carlos; Abrahão, Jairo Teixeira Mendes (Pesquisa Agropecuaria Brasileira, 1991)
The northern region of the State of Paraná presents favorable edaphic/climatic conditions for the cultivation of various species that can be used as green manure. Also, the existing agricultural system and infrastructure in those agricultural lands nowadays favor the practice of green manuring in winter. The cultivation of lupine (Lupinus albus L.) has been hampered by lack of technical information which would allow maximization of benefits from green manuring. With the purpose of studying the effects of times of sowing and spacing between plants on the production of phytomass from lupine, an experiment was carried out in Bandeirantes, PR, Brazil, in a Dusky Red Latosol eutrophic soil, using (4 x 4) factorial in randomized blocks with three replications. The treatments utilized four different times of sowing and four different spacings between lines, keeping population density at ten plants per linear meter in all treatments. It was observed that a reduction occurred in the production of phytomass when the sowing time was delayed and with a wider spacing between lines.